(untitled) (PANGEEA, 2025)
The systematic cadastral work in Romania involves the identification and measurement of buildings and their owners, their registration in the technical cadastral documents and their representation on cadastral plans, in order to be entered in the land register. These works are carried out within the National Program, a program whose purpose is the free registration of buildings in the integrated cadastre and land book system, the realization of the cadastral plan of buildings and the opening of land books at the level of all UATs. The paper presents the situation of the systematic registration of properties in Mureș county.